2019
DOI: 10.1186/s12879-019-3841-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Clostridium difficile infection in hospitalized adults and the first isolation of C. difficile PCR ribotype 027 in central China

Abstract: Background Clostridium difficile infection (CDI) is an emerging healthcare problem in the world. The purpose of this study was to perform a systematic epidemiological research of CDI in Tongji hospital, the central of China. Methods Stool samples from hospitalized adults suspected of CDI were enrolled. The diagnosis of CDI were based on the combination of clinical symptoms and laboratory results. Clinical features of CDI and non-CDI patients were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…Many of the C. difficile strains isolated from this patient population were highly resistant to rifampicin, clindamycin, erythromycin, ciprofloxacin, and ceftriaxone, and a large proportion were multidrug-resistant. Similar findings where more than half of the C. difficile isolates recovered were MDR have been associated with outbreaks ( Obuch-Woszczatyński et al., 2014 ; Krutova et al., 2015 ; Spigaglia, 2016 ; Ramírez-Vargas et al., 2017 ; Carman et al., 2018 ; Zhou et al., 2019 ). These findings highlight the significance of this pathogen in an African population previously considered to be at low CDI risk ( Roldan et al., 2018 ).…”
Section: Discussionsupporting
confidence: 71%
“…Many of the C. difficile strains isolated from this patient population were highly resistant to rifampicin, clindamycin, erythromycin, ciprofloxacin, and ceftriaxone, and a large proportion were multidrug-resistant. Similar findings where more than half of the C. difficile isolates recovered were MDR have been associated with outbreaks ( Obuch-Woszczatyński et al., 2014 ; Krutova et al., 2015 ; Spigaglia, 2016 ; Ramírez-Vargas et al., 2017 ; Carman et al., 2018 ; Zhou et al., 2019 ). These findings highlight the significance of this pathogen in an African population previously considered to be at low CDI risk ( Roldan et al., 2018 ).…”
Section: Discussionsupporting
confidence: 71%
“…C. difficile was found to carry adjacent mutS and mutL genes (CD630_19770 and CD630_19760), in addition to the mutS homolog mutS2 (CD630_07090). To construct a C. difficile mutator, we chose the strain ATCC 700057 (17) because it is non-pathogenic, lacking the toxin genes tcdA and tcdB (18), and is widely used for antibiotic susceptibility testing (12). We individually deleted mutS, mutL, mutS2 and the entire mutSL operon by allelic exchange using pMTL-SC7215; deletions were confirmed by PCR (19).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, investigations carried out in Chinese hospitals revealed that ST54 was the predominant type of CDI in diarrhea patients [31,32]. Also, according to our previous meta-analysis about the domestic molecular epidemiology, the epidemic strain of C. di cile isolated from diarrhea patients were mainly ST3, ST37 and ST54, accounting for 18.1%, 17.2% and 16.7%, respectively.…”
Section: Discussionmentioning
confidence: 98%